Higher Education Provided by the Service Warranty - Zīvarts, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Several issues are absorbed in practise and research of law applying, concerning the protection of consumers in „traditional” business and services. But issues conserning a warranty of higher education services, evoke indistinctness and difficulties in real practice, as there is no regulations in legislation of the Latvian Republic. It complicates customer protection in education, therefore creating untransparent and problematic service. Aim of the paper is to study warranty problems of higher education services and outline the possible solutions to these problems, also emphasizing the need tosolve these problems.